2012
DOI: 10.1111/j.1558-5646.2012.01619.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Stabilizing Selection: Expanding the Ornstein-Uhlenbeck Model of Adaptive Evolution

Abstract: Comparative methods used to study patterns of evolutionary change in a continuous trait on a phylogeny range from Brownian motion processes to models where the trait is assumed to evolve according to an Ornstein-Uhlenbeck (OU) process. Although these models have proved useful in a variety of contexts, they still do not cover all the scenarios biologists want to examine. For models based on the OU process, model complexity is restricted in current implementations by assuming that the rate of stochastic motion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
834
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 591 publications
(839 citation statements)
references
References 57 publications
(100 reference statements)
3
834
0
2
Order By: Relevance
“…As our preliminary analyses indicated that the estimates of u for spiny and spineless lineages were stabilized by assuming u at the root was distributed according to the stationary distribution of the OU process, we set root.station ¼ TRUE for all analyses. We checked the results of the OUWIE analyses to ensure that the eigenvalues of the Hessian were positive, as this is an indicator that the parameters were reliably estimated [58]. When a negative eigenvalue was found, we removed the results for that model and tree combination from the final dataset.…”
Section: (D) Generalized Ornstein-uhlenbeck Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…As our preliminary analyses indicated that the estimates of u for spiny and spineless lineages were stabilized by assuming u at the root was distributed according to the stationary distribution of the OU process, we set root.station ¼ TRUE for all analyses. We checked the results of the OUWIE analyses to ensure that the eigenvalues of the Hessian were positive, as this is an indicator that the parameters were reliably estimated [58]. When a negative eigenvalue was found, we removed the results for that model and tree combination from the final dataset.…”
Section: (D) Generalized Ornstein-uhlenbeck Modelsmentioning
confidence: 99%
“…We test our predictions using generalized Ornstein -Uhlenbeck (OU) models [57][58][59], which allow the presence and absence of spines to influence the primary optima of body depth or width (u), the stochastically constant rate of depth or width evolution (s 2 ), and/or the strength of pull towards the primary optima (a). u is the trait value reached by an 'infinite number of populations identical to the common ancestor evolving independently' [57, p. 1342] with spines in a fixed state, and thus quite different from the realized trait optimum in real populations.…”
Section: (D) Generalized Ornstein-uhlenbeck Modelsmentioning
confidence: 99%
“…OU processes have been widely studied and used in diverse areas of applied mathematics like biological modeling [23], [24], mathematical finance [25], [26] and statistical physics [27]. Using known results for the statistical distribution of the first time at which an OU process is above certain threshold [28], [27], [29], we propose a closed-form expression to estimate the error probability of the SC-LDPC code as a function of M , L and the gap to the ensemble's BP threshold.…”
Section: Csit] 25 May 2015mentioning
confidence: 99%
“…We fitted the new multi-c model in which s 2 t is constant but c varies between states. Finally, we fitted a multiple-optimum OU model (multi-OU) implemented in OUwie [42] that allows the optimum dewlap area to vary between geographical states, whereas s 2 and the strength of attraction to the optimum are constant. All six models account for intraspecific variability using species-specific standard errors.…”
Section: (E) Speciational Trait Evolutionmentioning
confidence: 99%